Time Value Of Money Dalam Tinjauan Konsep Keuangan Abd Al-Qadîm Zallûm Dan Pemikiran Ekonomi Taqiyuddîn Al-Nabhâni: The Time Value Of Money In The Financial Concept Of Abd Al-Qadîm Zallûm And The Economic Thought Of Taqiyuddîn Al-Nabhâni - Rendra Fahrurrozie; Misno (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
The concept of the time value of money, as recognized by conventional economics, posits that money available at the present time is worth more than the same amount in the future due to its potential earning capacity. This idea underlies the existence of interest rates and the fluctuating values of goods and services. The purpose of this study is to examine the perspectives of Al-Nabhani and Zallum on money and Islamic economics in relation to the time value of money. This research employs a qualitative method with a content analysis approach to the texts of Nizhâm Al-Iqtishâdy written by Taqiyuddin Al-Nabhani and Al-Amwâl authored by Abd Al-Qadim Zallum. The findings reveal distinctive viewpoints from these scholars: in Islam, money is defined as gold and silver with specific weights, and such currencies maintain stable values. Money is used as a standard measure for goods and services, serves as a medium of exchange, and the concept of the time value of money is rejected in Islamic law because it involves riba (interest), which is prohibited. Furthermore, hoarding money (kanz al-mâl) is forbidden, as is accumulating money to earn interest. Gold and silver can be lent (qardh) provided the transaction is immediate and in person. The time value of money concept does not exist in Islam because Islamic finance is based on gold and silver, which are stable, and this approach can offer solutions to global financial issues such as inflation. Keywords: Time value of money; Islamic economics; Gold and silver currency; interest; Hoarding money